An analysis of the design elements of the third renewable energy auction in Spain. Issue 3 (April 2018) - del Río, Pablo
Abstract : The third renewable electricity auction in Spain awarded 5037 MW in July 2017. This makes it the largest by awarded volume in Europe. The aim of this article is to describe this auction, analyse the choice of its design elements and provide a preliminary assessment of its outcome. It draws on several information sources, including relevant legislation, reports from the energy regulator, expert interviews and articles in the mass media. The results show some pros and cons in the choice of design elements. Whereas support costs have been minimized, its effectiveness in deploying renewable electricity in the country still has to be proven.